Polymorphisms of the CYP2D6 gene and its relationship with Plasmodium vivax relapses after chloroquine-primaquine treatment in Turbo, Colombia (2025)
Background: Plasmodium vivax relapse due to hypnozoites represents a significant mechanism for parasite persistence in the population. Primaquine (PQ), the drug of choice for eliminating hypnozoites, requires metabolic activation by Cytochrome P450-2D6 (CYP2D6). Genetic variations in CYP2D6 can alter PQ metabolism, potentially increasing the risk of relapses. This study aimed to determine CYP2D6 polymorphisms in subjects with Plasmodium vivax under supervised chloroquine-primaquine treatment and explore their association with relapses and PQ plasma levels. Methods: CYP2D6 phenotypes and genotypes were successfully determined for 71 out of 78 patients included in the study. Nine polymorphisms (SNPs and indels) and gene copy number variation were analyzed. The association between the CYP2D6 phenotype, P. vivax relapse over six months follow-up, and PQ plasma levels were explored. Results: Most diplotypes (81.7 %) were associated with normal (gNM-F) and ultrarapid (gUM) CYP2D6 metabolizers, while 18.3 % were associated with poor (gPM) and intermediate (gIM and gNM-S) metabolizers. The median plasma PQ concentration on day 2 was higher in impaired CYP2D6 activity group (poor/intermediate) compared normal metabolizers (normal/ultrarapid) (660.4 ng/ml vs 313.5 ng/ml; effect size r -0.51, 95 % CI -0.82 to 0.03). No significant difference was found in the hazard ratio (HR) of relapse between impaired and normal CYP2D6 activity (adjusted HR: 1.45; 95 % CI: 0.39-5.39). Conclusion: Impaired CYP2D6 activity phenotypes were frequent in individuals infected with P. vivax from an endemic region of Colombia. Further research is essential to elucidate the relationship between these phenotypes and P. vivax relapses, as suggested by this exploratory study.